BUDGETARY, POLITICAL AND SOCIOECONOMIC DETERMINANTS OF POLITICAL-PARTY SUCCESSION: EVIDENCE OF ELECTORAL BEHAVIOR IN BRAZILIAN MUNICIPALITIES - Rocha, Tiago Carneiro da; Araújo, Juliana Maria de; Brunozi Júnior, Antônio Carlos (Advances in Scientific and Applied Accounting, 2021)
Purpose: despite actions to intensify governance, transparency and accountability, there are still tendencies for government officials to manipulate fiscal and budget results and/or use political and socioeconomic information and direct their actions to achieve their own benefit, especially aiming political-party succession. Thus, the aim of this paper was to evaluate the influence of budgetary, political and socioeconomic aspects in the re-election of managers and in the reappointment of parties in Brazilian municipalities. Method: data were collected from Brazilian municipalities with a population above 100,000 inhabitants for the electoral cycles of 2004, 2008, 2012 and 2016. Data were submitted to Logistic Regression with panel data. Results: the probability of political-party succession is influenced by factors related to voters that reward those mayors who make more municipal investments, improving the quality of life of the population, which enable the minimization of inequalities through the transfer direct income and that have greater chances of establishing cooperation between the other spheres of government through party alignment. Contribution: the theoretical contribution is that informational asymmetry, public choices that involve the influence of human and institutional elements, and the voters' perception of social justice, are factors together that explain the political-party succession. As a practical contribution, it is argued that public administrators can use the state apparatus for their own benefits - leading to influence the voter's - which does not exercise social participation and/or does not use public and available information for adequate knowledge of the municipal management and governance.